Perceptions of farmers on health risks and risk reduction measures in wastewater-irrigated urban vegetable farming in Ghana - Keraita, Bernard N.; Drechsel, Pay; Konradsen, Flemming (2008)
Most irrigation water used in urban vegetable farming in Ghana is contaminated with untreated wastewater. This poses health risks to farmers and consumers. As part of a study to explore options for health risk reduction, this paper summarizes farmers' perceptions on health risks and possible risk reduction measures. Participatory research methods and techniques such as focus group discussions, in-depth interviews and visualization techniques were used for data collection based on methodological triangulation. The findings showed that farmers were aware that untreated wastewater posed health risks. Occupational health risks like skin infections were perceived to have the greatest risks and not nematode infections and bacterial diseases which are usually associated with wastewater irrigation. Possible health risks to consumers were rated very low and many farmers said that they were sensitized on this through media and projects. Farmers perceived many of the risk reduction measures suggested in the international guidelines as unsuitable and identified simple and low-cost measures which they could easily adopt. They were willing to adopt risk reduction measures to avoid further pressure from the media, authorities and the general public, especially if they had some incentives. These findings demonstrate the need to involve farmers as early as possible in intervention projects especially in informal farming practices, like urban agriculture, where restrictions are difficult to implement. This will ensure that their perceptions, constraints or any other required incentives for adopting interventions are considered, hence leading to developing more appropriate interventions.